2023
DOI: 10.1186/s40359-023-01121-6
|View full text |Cite
|
Sign up to set email alerts
|

School climate and academic burnout in medical students: a moderated mediation model of collective self-esteem and psychological capital

Abstract: Background The study burnout of medical students is more and more serious, which directly affects the study style of university and the learning quality of students. This has aroused the high attention of researchers and universities. This study aimed to explore the mechanism of the influence of school climate on academic burnout among medical students in Chinese cultural context. Methods 2411 medical students (50.52% female; mean age = 19.55, SD =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…Another reported 93.2% of surgical and medical residents in Makkah, Saudi Arabia, showed moderate to high imposter characteristics [ 39 ]. On the other hand, in Riyadh, the capital of Saudi Arabia, the prevalence of IS was shown to be 42.1% among King Saud University medical students [ 18 ]. While a recent Indian study found that 56.7% and 16.11% of students in medical colleges had IS and high SE, respectively [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another reported 93.2% of surgical and medical residents in Makkah, Saudi Arabia, showed moderate to high imposter characteristics [ 39 ]. On the other hand, in Riyadh, the capital of Saudi Arabia, the prevalence of IS was shown to be 42.1% among King Saud University medical students [ 18 ]. While a recent Indian study found that 56.7% and 16.11% of students in medical colleges had IS and high SE, respectively [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many stressors affect medical students, including social, medical school requirements and their fight for high achievements [ 13 17 ]. Moreover, the transition to the clinical years can be particularly challenging and cause students to suffer from low SE and confidence during this time [ 18 ]. As a result, they believe themselves to be less competent and intelligent than what they believe to be the case with their colleagues, teachers, parents, and society at large [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, by examining the outcomes of cross-sectional and longitudinal research, it is feasible to ascertain a potential correlation between mobile phone addiction and depression among individuals (13). Moreover, the adverse psychological state experienced by college students can manifest itself through a pivotal measure known as academic burnout, which profoundly influences the quality of their studies as well as their overall physical and mental well-being (14).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has mainly focused on two aspects: individual internal factors and external environmental factors. Individual internal factors include factors such as professional commitment ( Lian et al, 2006 ), coping styles ( Shi et al, 2023 ), academic anxiety ( Gao, 2023 ), loneliness ( Gu et al, 2023 ), self-esteem ( Yu et al, 2023 ), achievement motivation ( Atik and Çelik, 2021 ), personality ( Lee et al, 2017 ; Kong et al, 2021 ), positive psychological capital ( Wang et al, 2021 ), psychological resilience ( Gong et al, 2023 ), self-efficacy ( Chen et al, 2023 ), and core self-evaluation ( Dortaj, 2021 ). External environmental factors include stress ( Watson et al, 2008 ; Gong et al, 2023 ; Shi et al, 2023 ), social support ( Ye et al, 2021 ; Fu, 2023 ), parental education anxiety ( Kai et al, 2022 ), parental supervision ( Affuso et al, 2017 ), and parent–child attachment ( Zhang et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%